(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed to uncover the reality of the application of talent management in the Palestinian universities. Using the descriptive analytical methodology, the study targeted a sample of all staff in the Palestinian universities: The Islamic University, Al-Azhar University, University of Palestine, and Gaza University, which hold 206 supervisory positions. 166 questionnaires were recovered for analysis by 81%. The management of talent in the target universities was applied moderate level, and the absence of a specialized organizational unit in these universities to manage the talent. The dimensions of talent management were ranked decently due to the relative weight: talent recruitment and assignment, followed by talent managementplanning, then talent education and training, and finally talent retention. The results showed that there were no statistically significant differences in the responses of respondents on the application of talent management due to the university type variable (public or privet). Finally, the study revealed that there were no statistically significant differences in the responses of respondents on talent management due to gender variables and the nature of work, but there are differences in the age group in favor of category (30-40 years). The study recommends defining the concept of talent management within a specific organizational vision within the universities, while providing a precise description of it, by defining the procedures and systems that distinguish this concept from other concepts such as human resources management. The study also recommends that the official bodies, headed by the Ministry of Education, take care of the talented academic and administrative staff in the universities to avoid brain drain and direct investment in human resources in the course of sustainable development in Palestinian universities.